2022
DOI: 10.1038/s43856-022-00191-8
|View full text |Cite
|
Sign up to set email alerts
|

National and subnational short-term forecasting of COVID-19 in Germany and Poland during early 2021

Abstract: Background During the COVID-19 pandemic there has been a strong interest in forecasts of the short-term development of epidemiological indicators to inform decision makers. In this study we evaluate probabilistic real-time predictions of confirmed cases and deaths from COVID-19 in Germany and Poland for the period from January through April 2021. Methods We evaluate probabilistic real-time predictions of confirmed cases and deaths from COVID-19 in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…• Due to a meticulous generative description of the epidemic spread, the pDyn model achieves remarkable performance in predicting cases, hospitalizations, ICU hospitalizations, and deaths, as assessed by German and Polish COVID-19 Forecast Hub [24,25] and European COVID-19 Forecast Hub [54]. • Our generative ABM beneőts from complex internal states, enabling the implementation of mechanisms that phenomenological models cannot capture and allowing the incorporation of vast amounts of data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…• Due to a meticulous generative description of the epidemic spread, the pDyn model achieves remarkable performance in predicting cases, hospitalizations, ICU hospitalizations, and deaths, as assessed by German and Polish COVID-19 Forecast Hub [24,25] and European COVID-19 Forecast Hub [54]. • Our generative ABM beneőts from complex internal states, enabling the implementation of mechanisms that phenomenological models cannot capture and allowing the incorporation of vast amounts of data.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 126 SARS-CoV-2 ABMs revealed that only 17% were validated against real-world data, 3% were compared with other models, and 2% were systematically tested [22]. Furthermore, pDyn has continuously undergone external validation with real-world data [23] as part of the German and Polish COVID-19 Forecast Hub since November 2020 [24,25]. Individual ABMs, MOCOS [19] and pDyn, have achieved signiőcant performance improvements in long-term case forecasting in Poland due to their meticulous tailoring to speciőc country situations [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generating a combined estimate from a set of models is not a new concept; they are widely used across many disciplines, such as forecasting the weather [14], hydrology [15], flood losses [16], cancer prediction [17] and climate modelling [18]. Within infectious diseases, combined model estimates have been applied to modelling human immunodeficiency virus (HIV) [19], influenza [20], and Ebola [21,22] transmission and recently for outbreak analysis related to COVID-19 in the United States [23] and Europe [24].…”
Section: Introductionmentioning
confidence: 99%
“…Generating a combined estimate from a set of models is not a new concept; they are widely used across many disciplines; in forecasting the weather [41], hydrology [31], flood losses [22], in cancer prediction [59] and climate modelling [43]. Within infectious diseases, combined model estimates have been applied to modelling HIV [21], influenza [48] and Ebola [51, 13] transmission, and recently for outbreak analysis related to COVID-19 in the USA [53] and Europe [9].…”
Section: Introductionmentioning
confidence: 99%